Vitreous Vitae : St. Margaret of Antioch in Thirteenth-Century Stained Glass - Laverock, Ashley J., (Brill's Studies on Art, Art History, and Intellectual History ;, 2025)
In Vitreous Vitae: St. Margaret of Antioch in Thirteenth-Century Stained Glass , Ashley J. Laverock considers the representation of the virgin martyr St. Margaret in thirteenth-century stained-glass windows in Europe. These windows appeared at a moment when Margaret's cult was expanding but before the motif of the saint with the ragon became normative. They offer insight into the rich narrative potential of Margaret's life in a monumental medium seen by wide audiences. Examining these windows not only reveals shared emphases on Margaret's imitatio Christi , corporeal suffering, and encounters with the dragon and demon, but also shows how distinct site-specific hagiographies of Margaret were tailored to each church's context. Multi-faceted Margarets contributed to the wider cult of the saint.